The Construction of Galilee as a Place for the Historical Jesus—Part II - Moxnes, Halvor (Biblical theology bulletin, 2001)
In the Third Quest for the Historical Jesus, Galilee again came into the center of discussion, partly because of a general interest in local and regional studies, and partly because of the results of archaeological excavations. Many of the categories from the nineteenth century are still at work, e.g. nationalism (now identified with the state of Israel), but new perspectives from cultural studies and from economic and socio-political structures have gained importance. There are many areas of discussion, both in terms of traditional questions, like the degree of Hellenistic influence in Galilee, and new issues. Among the latter are methodological issues—e.g. concerning the interpretation of archaeological excavations and the use of social-science models in the reconstruction of ancient societies-and substantive issues of how to understand the relations between cities and peasant villages in Galilee. There are many challenges at the beginning of the twenty-first century, most pressing among them the need to see Galilee as part of the larger surrounding area and to study the role of Jesus in shaping the identity of Galilee in terms of resistance to existing power structures.